Performance Management and Quality Culture Reflection towards the Professional Teachers of the ASEAN Economic Community Era - Serli Serli (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2017)
Educational problems are so complex. It spurs so fast and moves dynamically through time and place, and those which are stagnant and rigid will be crushed. What Umar bin Khattab has said,